Lung Cancer Treatment Disparities in China: A Question in Need of an Answer. (15th September 2014) - Yang, Lu-Lu; Zhang, Xu-Chao; Yang, Xue-Ning; Yang, Jin-Ji; Wang, Zhen; Chen, Hua-Jun; Yan, Hong-Hong; Xu, Chong-Rui; Guan, Ji-Lin; He, Yan-Yan; Zhong, Wen-Zhao; An, She-Juan; et al.
Abstract: Background: Substantial progress has been made in the treatment of malignancies in the People's Republic of China in recent years. The goal of this study was to identify the extent to which national treatment guidelines are being used to customize patient care in lung cancer and to analyze the reasons for treatment disparities. Methods: Patient characteristics and treatments were investigated retrospectively for the period from October 2004 to January 2013 using the outpatient database of the Guangdong Lung Cancer Institute (GLCI) in China. Results: A total of 2, 535 outpatients with lung cancer were studied in this retrospective analysis. The treatment disparity was 45.3%. Overall, 20.6% of patients with stage I non-small cell lung cancer (NSCLC) were overtreated, and 20.1% of stage II patients were undertreated. Only 19.6% of stage IIIA patients and 30.7% of stage IIIB patients underwent the recommended combination of chemotherapy and radiotherapy, respectively. For advanced NSCLC, the greatest treatment disparity appeared in the second-line setting and beyond. Patients who were positive for epidermal growth factor receptor ( EGFR ) and receiving EGFR tyrosine kinase inhibitors experienced significant prolongation of survival compared with patients who were EGFR negative or whose EGFR mutation status was unknown (hazard ratio: 0.79; p = .037). The treatment disparities were significantly larger among patients aged younger than 65 years and in patients from developing regions compared with patients aged 65 years and older and from developed regions, respectively ( p < .001, p = .046). The difference in treatment disparity was statistically significant between GLCI and other hospitals ( p < .001). Conclusion: This retrospective study of a large number of patients from an outpatient oncology database demonstrated large disparities in the treatment of lung cancer in China. It is important to develop a new guideline for recommendations that are based on resource classification. Abstract : The goal of this study was to identify the extent to which national treatment guidelines are being used in the People's Republic of China to customize patient care in lung cancer and to analyze the reasons for treatment disparities. The results demonstrated large disparities in the treatment of lung cancer in China